Pendampingan Dan Pengembangan UMKM Di Kelurahan Kepanjenlor Melalui Re-Branding - Anisa Nur Cahyani; Aida Hamiyatul Masturo; Amiral Haqiqi; Nafalia Mulyanatul Jannah; Ladisa Putri, Dinda Rhaima (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
Micro, Small and Medium Enterprises (MSMEs) are business activities carried out by individuals or groups that aim to prosper the individuals or the groups. One of the problems faced by MSME is the lack of knowledge about the benefits of branding, low entrepreneurial skill, and most importantly is the lack of training or assistance related to technical branding strategies for MSME. Assistance and development through product re-branding is carried out in several steps, namely surveys and designing logos and supergraphics. The function of branding is to instill a positive image towards the consumers and MSMEs need to understand that. The Authors applied assistance method. The steps consist of observation, planning, implementation, and evaluation.